Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1176/appi.ps.201500507
|View full text |Cite
|
Sign up to set email alerts
|

The Business Case for Expanded Clozapine Utilization

Abstract: OBJECTIVE: In most settings, less than 25% of patients with treatment-resistant schizophrenia receive clozapine, the only medication proven effective for treatment-resistant schizophrenia. Therefore, a business case analysis was conducted to assess whether increasing clozapine utilization for treatment-resistant schizophrenia in a health care system would result in direct health care cost savings. METHODS: Veterans with treatment-resistant schizophrenia who were treated in the Veterans Health Administration (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…Thus increased outpatient costs may be outweighed by cost savings from reduced inpatient hospitalizations (36,37). A study described in a companion article (38) demonstrated that incremental increases in clozapine utilization could result in substantial cost savings, primarily through decreased use of inpatient admissions. Thus implementation of interventions derived from this study could more than pay for themselves, if they succeeded in increasing clozapine utilization for treatment-resistant schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus increased outpatient costs may be outweighed by cost savings from reduced inpatient hospitalizations (36,37). A study described in a companion article (38) demonstrated that incremental increases in clozapine utilization could result in substantial cost savings, primarily through decreased use of inpatient admissions. Thus implementation of interventions derived from this study could more than pay for themselves, if they succeeded in increasing clozapine utilization for treatment-resistant schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known effectiveness of this drug, series have established that less than 25% of patients with schizophrenia refractory to treatment are clozapine users, 10 this scenario being their main indication given the varied clinical benefits shown in this study. 11 That is why it is important to encourage its use in the indicated cases following a strict follow-up protocol.…”
Section: Discussionmentioning
confidence: 83%
“…A pesar de la efectividad conocida de este fár-maco, series han establecido que menos del 25% de los pacientes con Esquizofrenia refractaria a tratamiento son usuarios de clozapina 10 , siendo que este escenario es su mayor indicación dado los variados beneficios clínicos demostrados en este tipo de pacientes 11 . Es por esto que cobra relevancia el incentivar su uso en los casos indicados siguiendo un estricto protocolo de seguimiento.…”
Section: Discussionunclassified